2017
DOI: 10.1002/vms3.60
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of pimobendan and sildenafil therapy for severe pulmonary hypertension due to lung disease and hypoxia in 28 dogs (2007-2013)

Abstract: Pulmonary hypertension (PH) is the persistent abnormal increase in pulmonary artery (PA) pressure and in dogs is usually secondary to congenital disease causing pulmonary over circulation, chronic respiratory disease and elevated left atrial pressure. Sildenafil (SF) is a phosphodiesterase (PDE) V inhibitor that causes pulmonary artery (PA) vasodilation by increasing pulmonary vascular concentrations of cyclic guanosine monophosphate which subsequently increases the activity of endogenous nitric oxide. Pimoben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
0
13
1
1
Order By: Relevance
“…Most of the peer-reviewed veterinary medical literature regarding dogs with PH has evaluated the PDE5i, sildenafil. 40,42,43,52,80,84,[205][206][207] These studies suggest benefit with improvement of clinical signs, 52 quality of life, 52,84,207 exercise capacity, 84 Treatment strategies for PH are highly dependent on cause and chronicity of PH. Some PH-specific treatments (eg, pulmonary artery vasodilators such as PDE5i) might lead to acute pulmonary edema in some dogs with PH.…”
Section: Group 1 Pahmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the peer-reviewed veterinary medical literature regarding dogs with PH has evaluated the PDE5i, sildenafil. 40,42,43,52,80,84,[205][206][207] These studies suggest benefit with improvement of clinical signs, 52 quality of life, 52,84,207 exercise capacity, 84 Treatment strategies for PH are highly dependent on cause and chronicity of PH. Some PH-specific treatments (eg, pulmonary artery vasodilators such as PDE5i) might lead to acute pulmonary edema in some dogs with PH.…”
Section: Group 1 Pahmentioning
confidence: 99%
“…A PDE5i is recommended in group 3 dogs. 40,42,52,84,205,210 • Consensus in 7/7 members of the panel and 5/5 advisory reviewers Pimobendan: Pimobendan is an oral PDE3i with positive inotropic and systemic vasodilatory properties. It has been shown to improve RV systolic function following a single oral dose in healthy dogs.…”
Section: Group 1 Pahmentioning
confidence: 99%
See 1 more Smart Citation
“…Sildenafil is a highly selective PDE-5 inhibitor used to block the inactivation of cGMP by PDE-5, which leads to pulmonary arterial vasodilation (McLaughlin & McGoon, 2006). Several studies have demonstrated the benefits of sildenafil in dogs with PH caused by different pathogeneses such as respiratory disease and left heart disease, while the most recent retrospective study evaluated the effects of sildenafil and pimobendan in dogs with PH caused by lung disease or hypoxia, which showed overall poor survival rates (Bach et al, 2006;Brown, Davison, & Sleeper, 2010;Kellihan, Waller, Pinkos, Steinberg, & Bates, 2015;Kellum & Stepien, 2007;Murphy, Russell, Bianco, & Nakamura, 2017;Nakamura et al, 2011;Toyoshima, Kanemoto, Arai, & Toyoshima, 2007). In addition, the most guidelines from the human medicine for the management of PH advise against the use of PAH-approved therapies (which include sildenafil) in people with PH from left heart disease or PH from chronic lung Received: 15 September 2017 Basic information related to the pharmacokinetics of sildenafil in dogs is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…В ветеринарной кардиологии применение многих ЛАГ-специфичных препаратов ограничено их высокой стоимостью. Наиболее широко используют ингибитор ФДЭ-5-силденафил, относящийся к группе препаратов, влияющих на уровень оксида азота [3,5]. Кроме того, для лечения высокой легочной гипертензии у животных применяют селективный ингибитор ФДЭ-3-пимобендан, который снижает концентрацию эндотелина и тем самым приводит к расширению вен и артерий.…”
Section: Introductionunclassified